The Legal Culture of Samin Community of Family Law in Central Java - Nur Wakhidah; Zulfa Jamalie; Mujiburohman Abas; Raihanah Abdullah; Jalaluddin Jalaluddin (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2024)
This article seeks to examine the legal culture of the Samin community in relation to their preferences in family law, the persistence of the customary law in the community, and the transformations that have taken place in Samin family law. The data of this article is derived from an ethnographic study conducted at various Samin villages in Central Java between 2022 and 2023. Information was gathered via in-depth interviews, observation, and document analysis. The study's findings suggest that the government does not officially recognize marriage within the Samin community. However, the Samin family law has undergone a significant transformation. It underwent a substantial change which involved the government officially acknowledging the Samin beliefs. The research findings reveal symptoms of the Samin family law which underwent a transformation from customary law to local fiqh characterized by a mystical style. Efforts are being made to establish formal legal frameworks that accept the belief in God Almighty and incorporate legal practices. The legal negotiations led to the emergence of natural law plurality which in practice, is influenced by politics, social, and culture.